Evaluation of the stress level in female shelter dogs undergoing a seven-day adaptation period in experimental kennels - Henrique, Fernanda Vieira; Parentoni, Roberta Nunes; Leite, Angélica Ramalho Araújo; Lucena, Dayvid Vianês Farias [UNESP]; Dos Santos, Rodrigo Gustavo Dantas; de Souza, Almir Pereira; da Nóbrega Neto, Pedro Isidro (Medicina Veterinaria (UFRPE), 2019)
The objective of this study was to evaluate the stress level in female dogs in experimental kennels for seven days. Ten female dogs, weighing 12.96±3.19 kg and aged 3.4±2.6 years, from the Patoense Association for the Protection of Animals were used. Blood samples were collected to determine cortisol and blood glucose levels. Heart and respiratory rate, rectal temperature, and systolic, mean and diastolic arterial pressure were measured. To clinically evaluate stress, we used a Stress Composite Score. Stress was classified as discreet (score 0 to 6), moderate (scores 7-14), and intense (score >14). Statistical analyses were performed using the computer program Bioestat 5.0 at a 5% significance level. There was a decrease in the cortisol; however, statistically, only 144 (0.60±0.67 μg/dL) and 168 hours (0.55±0.55 μg/dL) after the arrival of the animals at the kennel did the cortisol differ from the baseline (2.78±2.7 μg/dL). Stress was classified as discreet in all time points (scores <6). The female dogs of this experiment did not perceive the admission to the kennel as a potential stressor. It is suggested that six days is enough for female dogs to adapt to a new environment.
Avaliação do nível de estresse em cadelas de abrigo submetidas a um período de adaptação de sete dias em canis experimentais
Keywords: Blood glucose; Canine; Cortisol